To distribute the expression \((2x + 3)(3x - 1)\), we will apply the distributive property (also known as the FOIL method for binomials).
Starting with your provided part:
- \(2x \cdot 3 = 6x\)
Now we continue with the rest of the distribution:
- \(2x \cdot (-1) = -2x\)
- \(3 \cdot 3x = 9x\)
- \(3 \cdot (-1) = -3\)
Putting it all together, the complete distribution of \((2x + 3)(3x - 1)\) is:
\[ 6x - 2x + 9x - 3 \]
So the result of the distribution (without combining like terms) is:
\[ 6x - 2x + 9x - 3 \]